EROTIC KAFKA - Gabriel Sausen Feil (Travessias, 2007)
This article seeks to assert Kafka as an erotic. Eroticism, on the way it has been understood here, is linked to transgression, and this writer, according to Gilles Deleuze and Flix Guattari, does not cease to operate transgressions, to make a segment get connected with another unimaginable by that time. This transaction takes place, mainly through the replacement of the conjugal contract by a diabolical pact, and by the process of depersonalisation of its characters. Furthermore, the article also deals in saying that between Kafka and other authors, such as Sacher-Masoch, Pierre Klossowski (these ones recognized as erotics), there is a characteristic in common: the creation of a procedure of